Brain structural alterations in young girls with Rett syndrome: A voxel-based morphometry and tract-based spatial statistics study - Li, Dongyun; Mei, Lianni; Li, Huiping; Hu, Chunchun; Zhou, Bingrui; Zhang, Kaifeng; Qiao, Zhongwei; Xu, Xiu; Xu, Qiong (Frontiers in Neuroinformatics, 2022)
Rett syndrome (RTT) is a neurodevelopmental disorder caused by loss-of-function variants in MECP2 gene, currently with no cure. Neuroimaging is a key instrument to obtain both structural and functional information of the in vivo brain, non-invasively. Multiple approaches of MRI scans have been utilized effectively in RTT patients to understand the possible pathological basis. The present study combined developmental evaluations, clinical severity, T1 weighted imaging and diffusion tensor imaging, aiming to explore the structural alterations in cohorts of young girls with RTT, idiopathic autism spectrum disorder (ASD), or typical development. Voxel-based morphometry (VBM) was to determine the voxel-wised volumetric characteristics of gray matter while tract-based spatial statistics (SPSS) was to obtain voxel-wised properties of white matter. Finally, correlation analysis between the brain structural alterations and the clinical evaluations was performed. In RTT group, VBM revealed decreased gray matter volume in insula, frontal cortex, calcarine and limbic/paralimbic regions; TBSS demonstrated decreased FA and increased MD mainly in corpus callosum and other projection and association fibers such as superior longitudinal fasciculus, corona radiata, and etc. The social impairment quotient and clinical severity were associated with these morphometric alterations. This monogenic study with early stage of RTT may provide some valuable guidance for understanding the disease pathogenesis. At the same time, the pediatric-adjusted analytic pipelines for VBM and TBSS were introduced for significant improvement over classical approaches for MRI scans in children.